Determinants of Uncharacteristic Loans in Savings and Loan Units Menara Desa Pematang Duku (USP) - Muhammad Isa Selamat; Khodijah Ishak; Husnul Khotimah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This study aims to determine the determinants of Bad Credit in the Savings and Loan Unit (USP) from an Islamic Economic Perspective from the Character, Economic Conditions and Ability to Manage Credit to the Savings and Loans Unit (USP). This is a bad credit study in the Savings and Loans Unit (USP) which was then analyzed using SPSS 23 software. As for the normality test, it was obtained 0.122 > 0.05. From these results it can be seen that it is normally distributed. In the multiple linear regression test, the character has a significant effect on bad loans of 0.872> 0.05 with tcount < ttable -0.163 < 2.073, economic conditions have a significant effect on bad loans of 0.001 <0.05 with tcount < ttable -3.844 < 2.073, the ability to manage credit has a significant effect on bad loans of 0.665 <0.05 with tcount <ttable -0.439 <2.073. From the coefficient of determination test, it is found that the influence of character (X1), economic conditions (X2), and ability to manage credit (X3) on bad loans (Y) is 46.0% and the remaining 54.0% is influenced by other variables such as credit term, natural disasters, credit supervision, and others